Retos epistemológicos para la producción de conocimiento en administración caos, complejidad y organización. (2021)
This paper shows the existing tension among the dominant vision of the globalization as a unique universal system and the vision of a resulting chaotic structure in a global economy , that can only be understood from a network morphology that turns out to be definitively «AUTOPOIESICA « and complex.